Paris Agreement : United Nations framework convention on climate change; reproduced by Public Forum Guyana (PFG) (Policy Forum Guyana GeorgetownGY, 2015)
Presents a reproduction of the text of the UN Climate Change agreement. Includes the dates signed, ratified and entered into force for Guyana.
Keywords: CLIMATE CHANGE